Dealing with “the Destitute and the Wretched”: The Protestant House of Industry and Refuge in Nineteenth-Century Montreal - Harvey, Janice (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2001)
AbstractThis paper is an examination of the responses of Montreal's anglophone elite to poverty and homelessness. It studies the Montreal Protestant House of Industry and Refuge from its opening in 1863 to 1900. Influenced by the emerging liberal ideology that interpreted charity as moral weakness, the Board of Directors of this private charity imposed a work test to restrict aid and to “reform” recipients, and provided minimal living conditions in its shelters. As they gained experience in relief provision, the Directors grappled with the contradictions raised by their moral condemnation of the unemployed and the reality of unemployment and homelessness. Ultimately, their humanitarianism and Christian spirit prevented them from allowing their fellow citizens to starve on the streets.